N6-Methyladenosine RNA Modification in Inflammation: Roles, Mechanisms, and Applications - Luo, Jiahui; Xu, Tao; Sun, Kai (Frontiers in Cell and Developmental Biology, 2021)
N6-methyladenosine (m6A) is the most prevalent internal mRNA modification. m6A can be installed by the methyltransferase complex and removed by demethylases, which are involved in regulating post-transcriptional expression of target genes. RNA methylation is linked to various inflammatory states, including autoimmunity, infection, metabolic disease, cancer, neurodegenerative diseases, heart diseases, and bone diseases. However, systematic knowledge of the relationship between m6A modification and inflammation in human diseases remains unclear. In this review, we will discuss the association between m6A modification and inflammatory response in diseases, especially the role, mechanisms, and potential clinical application of m6A as a biomarker and therapeutic target for inflammatory diseases.